2010
DOI: 10.1063/1.3360219
|View full text |Cite
|
Sign up to set email alerts
|

Energy-harvesting device with mechanical frequency-up conversion mechanism for increased power efficiency and wideband operation

Abstract: Frequency up-converted wide bandwidth piezoelectric energy harvester using mechanical impact A magnetoelectric energy harvester with the magnetic coupling to enhance the output performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
113
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(114 citation statements)
references
References 7 publications
(1 reference statement)
1
113
0
Order By: Relevance
“…9,10 However, power densities in such designs are reduced due to the increased system volumes of the VEHs. Nonlinear techniques, such as bi-stable systems 11,12 and Duffing oscillation, [13][14][15] can effectively improve the frequency response with a broad bandwidth, but nonlinear vibrations of the harvesters would happen only when the environmental vibration intensity is large enough to induce the stretching force in the VEH's beam. Resonant frequency tuning [16][17][18] also has been investigated, with passive or active tuning by adjusting the preload of VEH's beam.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, power densities in such designs are reduced due to the increased system volumes of the VEHs. Nonlinear techniques, such as bi-stable systems 11,12 and Duffing oscillation, [13][14][15] can effectively improve the frequency response with a broad bandwidth, but nonlinear vibrations of the harvesters would happen only when the environmental vibration intensity is large enough to induce the stretching force in the VEH's beam. Resonant frequency tuning [16][17][18] also has been investigated, with passive or active tuning by adjusting the preload of VEH's beam.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hybrid nanogenerators combining several mechanisms, such as the use of piezoelectric and triboelectric principles to convert mechanical energy into electricity, have been attracting an increasing amount of attention, [10,[18][19][20][21][22][23][24][25][26][27][28][29][30]. Mahmoudi et al reported a multiphysics hybrid piezoelectric-electromagnetic vibration energy harvester with a nonlinear equation of motion for an enhancement power density up to 84% [20].…”
Section: Introductionmentioning
confidence: 99%
“…With the objective of harvesting vibration energy, a great deal of researches on vibration-to-electric transformation using piezoelectric [1][2], electrostatic [3] and electromagnetic [4][5] transductions have been done in recent years. Compared with a piezoelectric and an electrostatic generator, an electromagnetic harvester is with a higher achievable energy density.…”
Section: Introductionmentioning
confidence: 99%